Defects of welded joints of the wire, causing breakages during drawing - E. S. Seregina; T. N. Ayupova (Литьë и металлургия)
Based on the research experience of the wire raptures all weld defects are systematized. These stydies were done during the rough-the middle wire drawing and bronzing. The defects which most often occur breakages of wire were listed and requirements to the weld seam were established.